The gratifications of local television sports programs from the audience's point of view Analytical study for the period from 1/7/2022 to 01/10/2022 (Al-Academy, 2023)
The issue of sports media and its role in winning sports and non-sports fans and unifying them towards various issues and events is one of the important topics that have begun to occupy many countries and governments in the world and allocate appropriate spaces for it and provide it with sufficient funds and budgets to advance this reality...Especially since the concept of the sports official has It changed a lot and turned into an economic concept rather than a sport one through the investment in the field of sports and the entry of capital and contributes to the prosperity of the countries interested in this field.It is important that includes profit and loss in addition to knowing how to employ and win the masses and employ the appropriate human resources to achieve sports achievements and activate this clearly and clearly through more than one axis. Programs by uniting the public in the face of important sporting events related to national issues, strengthening national belonging to the homeland, and making society more coherent and unified